The Influence of Teacher Professionalism and Learning Environment on Improving the Quality of Foreign Language Learning - Alawiyah, Izza Nur; Al Fatih, Muhammad (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
The purpose of this study was to determine whether there is an influence between teacher professionalism and the learning environment on improving the quality of foreign language learning of students in Islamic boarding schools. This study uses a quantitative method with an ex post facto research type. The research data were distributed through questionnaires with 59 students as respondents. The analysis showed that the results of the simultaneous F test with a significance value of 0.002 (p <0.005) and the results of the calculated F 6.793> F table 3.165, then Ho was rejected, and Ha was accepted. The results of the determination coefficient test were 0.195 or 19.5%, which means that the influence of the independent variables of teacher professionalism (X1) and learning environment (X2) on the dependent variable of improving the quality of foreign language learning (Y) was 19.5%, the remaining 80.5% was influenced by other factors not examined in this study. The study results indicate that teacher professionalism and a well-managed learning environment will improve the quality of foreign language learning for students in Islamic boarding schools. This finding confirms that improving teacher professionalism and creating a conducive learning environment is important to improving students' foreign language learning quality.